DIALECTICS OF NATIONAL AND UNIVERSAL VALUES IN SPIRITUAL PROPAGANDA - Temirova Odina Muhiddin qizi (American Journals, 2022)
The idea of universal values and norms has a long history in the world philosophical thought, in the XX century it was discussed quite sharply, and recently it has become a factor of mass consciousness of modern society. However, despite the discussion over many epochs of human culture, a sufficiently clear and convincing solution has not yet been found to the problem of universal values.
Keywords: spirituality, national value, universal value, propaganda, spiritual propaganda, education, spiritual heritage.